2004
DOI: 10.1086/381599
|View full text |Cite
|
Sign up to set email alerts
|

Limitations to Successful Investigation and Reporting of Foodborne Outbreaks: An Analysis of Foodborne Disease Outbreaks in FoodNet Catchment Areas, 1998–1999

Abstract: To better understand factors associated with confirming the etiologic organism and identifying the food vehicle responsible for foodborne-disease outbreaks, we examined data from outbreaks reported in 1998 and 1999 through active surveillance by Foodborne Disease Active Surveillance Network (FoodNet) surveillance areas in 7 states. In 71% of these outbreaks, no confirmed etiology was identified, and in 46%, no suspected food vehicle was identified. Outbreaks involving > or =10 cases were significantly more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 8 publications
3
34
0
1
Order By: Relevance
“…Current budget cuts at local and state levels coupled with shrinking laboratory staff numbers compound the task of producing a fast and sensitive diagnosis. Jones et al determined that 71% of ADD outbreaks had no confirmed etiology and that in 45%, the suspected food vehicle could not be identified due to inadequate resources for epidemiologic investigation, collection, and fast testing of clinical samples, thus limiting successful food-borne outbreak investigations (8).…”
mentioning
confidence: 99%
“…Current budget cuts at local and state levels coupled with shrinking laboratory staff numbers compound the task of producing a fast and sensitive diagnosis. Jones et al determined that 71% of ADD outbreaks had no confirmed etiology and that in 45%, the suspected food vehicle could not be identified due to inadequate resources for epidemiologic investigation, collection, and fast testing of clinical samples, thus limiting successful food-borne outbreak investigations (8).…”
mentioning
confidence: 99%
“…Despite extensive experiences and development in the diagnosis and management of epidemics, numerous epidemic investigations are terminated without satisfying results [3,4,7]. The reasons, especially in developing countries, include insufficient guidelines for diseases surveillance and epidemic investigation, delayed and improper response due to lack of required facilities and insufficient training of health staff [4].…”
Section: Discussionmentioning
confidence: 99%
“…Gastroenteritis, an infectious disease transmitted predominantly via food and water, is one of the most common communicable diseases [1,2]. However, many investigations into gastrointestinal disease outbreaks and epidemics fail to reach conclusive and unbiased results due to a number of issues including improper investigation guidelines, delayed response and shortage of laboratory and logistic facilities [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, there are an estimated 119,320 episodes of foodborne illnesses each year, accounting for a rate of 3,241 per 100,000 population (Scott et al, 2000). Foodborne-illness outbreaks are under-reported and it is estimated that 68% of foodborneillness outbreaks are notified to the Centers for Disease Control and Prevention (Jones et al, 2004). Even during foodborne illness outbreaks, only a small proportion of the total number of cases is reported.…”
Section: Public Health Impactmentioning
confidence: 99%
“…In the United States, during 1993-1997, an average of 550 foodborne illness outbreaks was reported annually. Each outbreak had an average of 31 cases (Jones et al, 2004). Foodborne illnesses also play an important role in new and emerging infections.…”
Section: Public Health Impactmentioning
confidence: 99%